2012
DOI: 10.11646/zootaxa.3318.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Epinotia cinereana (Haworth, 1811) bona sp., a Holarctic tortricid distinct from E. nisella (Clerck, 1759) (Lepidoptera: Tortricidae: Eucosmini) as evidenced by DNA barcodes, morphology and life history

Abstract: DNA barcodes of European tortricid moths identified as Epinotia nisella (Clerck, 1759) were found to comprise two ge-netically distinct clusters. These coincided with E. nisella and E. cinereana (Haworth, 1811) (sp. rev.), the latter havingbeen considered a synonym of the former for several decades. Comparing these DNA barcodes with those of North Amer-ican Epinotia showed that both species are Holarctic. The North American Proteopteryx criddleana Kearfott, 1907 is anew junior synonym of E. cinereana (syn. nov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 0 publications
0
21
0
2
Order By: Relevance
“…Our results highlight the need to carry out additional intraspecific studies looking at patterns of both morphological and genetic variability within species across their ranges, which can reveal overlooked diversity and new species (Huemer 2011, Huemer and Mutanen 2012, Mutanen et al 2012a, b, c), in regions that are thought to be well studied.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Our results highlight the need to carry out additional intraspecific studies looking at patterns of both morphological and genetic variability within species across their ranges, which can reveal overlooked diversity and new species (Huemer 2011, Huemer and Mutanen 2012, Mutanen et al 2012a, b, c), in regions that are thought to be well studied.…”
Section: Discussionmentioning
confidence: 88%
“…The integration of genetic data into taxonomic studies, especially with the advance of DNA barcoding campaigns (the construction of libraries of DNA barcodes for identification), has revealed many cases of cryptic or overlooked species in the tropics (Janzen et al 2009, 2012), but also in some of the most studied regions such as Europe (Mutanen et al 2012a, b, c, 2013). …”
Section: Introductionmentioning
confidence: 99%
“…Although the new species were retrospectively observed to be unique in their morphology, we are convinced that several of them would have remained undetected for some time without DNA barcodes. Numerous recent taxonomic studies have demonstrated the usefulness of DNA barcoding in initial detection of taxa that have been recognized as new after closer examination33343536373839404142. Our study is rare in the breadth of sampling and the independent validation of genetic results with morphological evidence, including the large-scale examination of genital structures.…”
Section: Discussionmentioning
confidence: 90%
“…Many other species first detected by DNA differences have retrospectively been shown to be morphologically distinguishable, representing cases of cryptic or morphologically closely similar species33343536373839404142 (whether a species is similar enough to be ‘cryptic’ or not is a fine line). A remarkable amount of DNA barcode data has been generated during recent years in association with the campaigns of the International Barcode of Life Project (iBOL, http://ibol.org/).…”
mentioning
confidence: 99%
“…However, some specimens in four BINs (BOLD:AAB2197, BOLD:AAC8630, BOLD:ACM4218, BOLD:ACM4689, also labelled as ‘ lixella -group I–IV in Fig. 14) were characterized by pronounced barcode divergence similar or exceeding those of described species, suggesting that they constituted putative undescribed diversity, as has been documented elsewhere in Lepidoptera (for examples, see Huemer and Hebert 2011, Huemer et al 2012, Huemer et al 2013, Kaila and Mutanen 2012, Landry and Hebert 2013, Mutanen et al 2012a, b, Segerer et al 2011, Wilson et al 2010). Additionally, specimens identified as Coleophora lixella on the basis of genitalia separated into three different BINs which showed the shortest inter-group distances (1.4–1.6%) among all species analyzed.…”
Section: Dna Barcode Analysismentioning
confidence: 69%